1990
DOI: 10.1155/1990/280467
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric RSV Infection During Two Winter Seasons in British Columbia: A Role for Subgroup Analysis in Young Children?

Abstract: Using a panel of eight monoclonal antibodies directed against the G, F and NP proteins of respiratory syncytial virus, 167 virus isolates from nasopharyngeal washing cultures at British Columbia Children's Hospital during two consecutive epidemics were subgrouped. Slides made and frozen at the time of virus isolation or prepared from recovered frozen passage material, were assayed by indirect immunofluorescence. Of 85 strains tested in 1987-88, 54 (64%) were subgroup A, and 31 (36%) subgroup B. By contrast, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Several studies have evaluated differences in clinical severity between subgroups A and B, but investigations have given varying results in different locations. In about half of these studies, the RSV subtype was not correlated significantly with severity [Hendry et al, 1986[Hendry et al, , 1987Monto and Ohmit, 1989;Russi et al, 1989;Wilson et al, 1990;Tsutsumi et al, 1991;McIntosh et al, 1993;Wang et al, 1995;Kneyber et al, 1996;Bergstrasser et al, 1998;DeVincenzo, 2004]. Other studies have found RSV-A McConnochie et al, 1990;Walsh et al, 1997;Imaz et al, 2000;Papadopoulos et al, 2004] or B [Hornsleth et al, 1998] as the most severe pathogen; however, in some cases, this effect was lost when confounders were taken into account in logistic regression models.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have evaluated differences in clinical severity between subgroups A and B, but investigations have given varying results in different locations. In about half of these studies, the RSV subtype was not correlated significantly with severity [Hendry et al, 1986[Hendry et al, , 1987Monto and Ohmit, 1989;Russi et al, 1989;Wilson et al, 1990;Tsutsumi et al, 1991;McIntosh et al, 1993;Wang et al, 1995;Kneyber et al, 1996;Bergstrasser et al, 1998;DeVincenzo, 2004]. Other studies have found RSV-A McConnochie et al, 1990;Walsh et al, 1997;Imaz et al, 2000;Papadopoulos et al, 2004] or B [Hornsleth et al, 1998] as the most severe pathogen; however, in some cases, this effect was lost when confounders were taken into account in logistic regression models.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of hospitalized infants predating the introduction of molecular methods, have suggested that RSV-A was more likely to cause severe illness or necessitate intensive care when compared to RSV-B [2426]. In contrast, and in line with multiple early studies, Monto and Ohmit found no differences in illness characteristics between the two subtypes in a community setting [2731]. More recent studies describing the relationship between RSV subtype, viral load, and illness severity have focused primarily on hospitalized infant populations and report varied results.…”
Section: Discussionmentioning
confidence: 93%
“…Grouping was based on substantial genetic heterogeneity (19, 33,77,131), especially involving the G glycoprotein, a protein putatively responsible for RSV attachment to cells. Antigenic variability of RSV strains and its possible role in explaining the phenomenon of reinfection (95,96,139,144,147), apparent differences in disease severity (62,88,89,98), and RSV epidemiology (4,126,128,137) are under investigation.…”
Section: Phenotypic Variationmentioning
confidence: 99%